Tindak Tutur Direktif pada Video Pembelajaran Teks Drama Kelas XI di Kanal Youtube - Putri, Dziza Firdiani; Hidayah, Nasik; Neina, Qurrota Ayu; Saragih, Desi Karolina; Utomo, Asep Purwo Yudi (Kajian Bahasa dan Sastra (KABASTRA), 2023)
Qualitative descriptive method was used in the analysis of directive speech acts of this study between teachers and students in learning Indonesian for the material for staging drama scripts at the high school (SMA) level. This study aims to describe the various forms of directive speech acts in high school (SMA) learning. The research method of this article is a qualitative descriptive study. The data source is the directive speech acts of Indonesian language learning videos in the classroom between female teachers and class XI students uploaded on the YouTube channel. The technique in this study to obtain data is a documentation technique in the form of note-taking. The results of this study include forms of direct and indirect directive speech acts. This study shows that in classroom learning there are many directive speech acts, and the more dominant speech acts used in the teaching and learning process in the classroom are direct directive speech acts. Researchers found as many as 19 speech acts. There are 18 direct directive speech acts consisting of 10 directive commanding speech acts on the target, 2 direct commanding speech acts with argumentation, and 6 direct directive speech acts asking for the target. Meanwhile, indirect directive speech acts were not found so much that only 1 speech act was found, namely indirect speech acts in the form of commanding with the mode of telling.